1988
DOI: 10.1103/physrevlett.60.1178
|View full text |Cite
|
Sign up to set email alerts
|

Specific heat of single crystals ofYBa2Cu3et al.

Abstract: Gaussian fluctuations have been observed in the specific heat of two single crystals of YBa2Cu3C>7-$. Deviations from a BCS-type step are well accounted for by 3D Gaussian fluctuations whose amplitude ratio, in the cleaner sample, implies that the number of order-parameter components is 7 ± 2. This result is inconsistent with an 0(2) Ginzburg-Landau theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(25 citation statements)
references
References 9 publications
1
23
1
Order By: Relevance
“…Large temperature intervals dominated by thermodynamic fluctuations are observed in equilibrium and transport properties of the high-Tc cuprates (HTSC) near the normal-superconducting transition (1,2]. The study of Gaussian fluctuations, which are observed far from Tc, gives information on the effective dimensionality for superconductivity in the HTSC [1,3,4].…”
Section: Introductionmentioning
confidence: 98%
“…Large temperature intervals dominated by thermodynamic fluctuations are observed in equilibrium and transport properties of the high-Tc cuprates (HTSC) near the normal-superconducting transition (1,2]. The study of Gaussian fluctuations, which are observed far from Tc, gives information on the effective dimensionality for superconductivity in the HTSC [1,3,4].…”
Section: Introductionmentioning
confidence: 98%
“…Other behavior is also possible. For example, in both conventional low-T C (superconducting transition temperature) superconductors 33 , as well as in cuprates [34][35][36] , there have been reports of enhanced T C near TBs. This implies that vortices can be repelled from TBs.…”
Section: Introductionmentioning
confidence: 99%
“…The component 1.43γ(1 -I-1.83t) describes BCS specific heat excess above the normal electronic component in the vicinity of Tc [10]. The last term describes Gaussian fluctuations [4,10]. The results f fitting for Dy and Tl samples are shown in Fig.…”
Section: G Gritzner and M Mairmentioning
confidence: 91%
“…magnetic contribution from either Dy+ 3 ions or antiferromagnetic correlations of Cu+2 sublattice) in a region close to the transition. The component 1.43γ(1 -I-1.83t) describes BCS specific heat excess above the normal electronic component in the vicinity of Tc [10]. The last term describes Gaussian fluctuations [4,10].…”
Section: G Gritzner and M Mairmentioning
confidence: 99%